Comprehensive assessment of phytometabolites and health benefits of Geographical Indication turmeric in India: Phytometabolites and health benefits of G. I. turmeric - Jose, Dona Ann; Bhabhina, N M; Leela, N K; Vishudha, M; Aarthi, S; Prasath, D (Journal of Spices and Aromatic Crops, 2022)
The interest and demand for the Geographical Indication (GI) turmeric have increased significantly in recent years as research unfolds their unique benefits. Still, their comprehensive and comparative metabolite profile remains to be analysed in detail from a nutritional perspective. This investigation reports phytochemical constituents, nutraceuticals, and bioactivities of four GI turmeric (Erode turmeric, Kandhamal haldi, Waigaon turmeric and Sangli turmeric) in India. The results revealed considerable differences in major quality parameters viz., essential oil (4.00-5.60%), oleoresin (8.36-18.12%) and curcuminoids (2.23-5.50%). Among the GIs, Waigaon turmeric was superior in terms of quality parameters and rhizome traits. The Erode turmeric contained significantly high protein (4.64%) and several minerals (K, Ca, Fe and Mg). The IC50 values of DPPH scavenging assays (160.72 – 194.25 μg ml-1) and α-glucosidase inhibitory assays (126.50 – 146.57 μg ml-1) ensured the potent antioxidant and anti-diabetic activities of GI turmeric. The GC-MS profile of essential oil unveiled six major compounds such as, ar-turmerone, β-sesquiphellandrene, α-zingiberene, α-curcumene, α-turmerone, and curlone. The brightest yellow colour was observed in Sangli turmeric and dark orange in Waigon turmeric, based on L*, a* and b* values. All the four GI turmeric varieties are good sources of spice for people to consume but Waigaon turmeric was found to be superior among them.